Charles Hill's The First Chapters: Dividing the Text of Scripture in Codex Vaticanus and Its Predecessors A Review Article. - Hsieh, Nelson S. (TC: A Journal of Biblical Textual Criticism, 2024)
Charles Hill's The First Chapters provides the first ever monograph- length treatment of Codex Vaticanus's chapter numbering. This article engages with three of Hill's main arguments: (1) Hill argues that the chapter numbering was added during the original production of the manuscript. I agree, and I simplify Hill's argument and provide additional palaeographical evidence. (2) Hill argues that Vaticanus's chapter numbering derives from earlier attempts at textual division found in papyri such as P75. I disagree, except perhaps in John 1-5. (3) Hill argues that the most likely provenance for Vaticanus's chapter numbering is third-century Caesarea and that perhaps Origen, Eusebius, and/or Pamphilus created the system. I tentatively agree based on the colophons found in some medieval manuscripts.